2015
DOI: 10.1007/s12110-015-9250-7
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and Navigation among the Yucatec Maya

Abstract: Sex differences in range size and navigation are widely reported, with males traveling farther than females, being less spatially anxious, and in many studies navigating more effectively. One explanation holds that these differences are the result of sexual selection, with larger ranges conferring mating benefits on males, while another explanation focuses on greater parenting costs that large ranges impose on reproductive-aged females. We evaluated these arguments with data from a community of highly monogamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…While the subsistence economy changed over the 20-year interval, many aspects of reproduction remained the same. During both time periods (1992 and 2011), Maya marriages can be described as life-long and monogamous (Cashdan et al, 2016). Some women (∼25% in the 2011 sample) currently use birth control, although mean completed fertility has only slightly declined over the past 20 years (1992 mean = 7.5 ± 1.74, n = 24; 2011 mean = 6.1 ± 3.01, n = 40).…”
Section: The Populationmentioning
confidence: 99%
“…While the subsistence economy changed over the 20-year interval, many aspects of reproduction remained the same. During both time periods (1992 and 2011), Maya marriages can be described as life-long and monogamous (Cashdan et al, 2016). Some women (∼25% in the 2011 sample) currently use birth control, although mean completed fertility has only slightly declined over the past 20 years (1992 mean = 7.5 ± 1.74, n = 24; 2011 mean = 6.1 ± 3.01, n = 40).…”
Section: The Populationmentioning
confidence: 99%
“…Recently the Maya have experienced rapid socioeconomic changes due to the growth of lowland towns, creation of new roads, improved transport, greater availability of schools, and increased contact with Mexican and global cultures [ 38 ]. These changes allowed many individuals, particularly unmarried males, to work for wages in nearby Spanish-speaking urban centers, such as Cancun or Playa del Carmen [ 39 ]. However, wage jobs are seen as a supplement to agricultural work, needed to increase household productivity in times of need and not as a replacement for it ( S1 Text ).…”
Section: Methodsmentioning
confidence: 99%
“…Though considerable prior work has aimed to identify and relate individual differences, surprisingly little work has focused on the characteristics of a navigator's home environment, as well as on the cultural and daily navigational demand of daily life, as an explanation for why individual differences may be observed. However, a few classic studies, along with a wide range of recent evidence from the Spatial Cognition and Navigation (SCAN) lab have demonstrated how local environments, economic requirements and particular ecologies, and social norms and cultural institutions shape human spatial cognitive abilities (Barhorst-Cates et al 2021;Cashdan et al 2016;Crittenden et al 2021;Davis and Cashdan 2019). First, in the Padua and Salt Lake City study, Barhorst-Cates et al (2021) found through interviews focused on daily activities and city mapping that the greatest influence on navigation strategies and accuracy between the two WEIRD populations was home environmental experiences.…”
Section: Spatial Navigationmentioning
confidence: 99%